2017
DOI: 10.1007/s00228-017-2291-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis

Abstract: Probiotics are recommended to supplement triple therapy in pediatrics, and the effectiveness of triple therapy is associated with specific probiotic supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 35 publications
3
52
1
7
Order By: Relevance
“…Previous meta-analyses on probioticsupplemented triple therapy for H. pylori infection in children showed that the efficacy and safety appeared to be different according to the different probiotics used. Feng et al 30 There was no significant difference between the groups in terms of eradication rate and symptom relief, so the synbiotic addition showed no superiority.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous meta-analyses on probioticsupplemented triple therapy for H. pylori infection in children showed that the efficacy and safety appeared to be different according to the different probiotics used. Feng et al 30 There was no significant difference between the groups in terms of eradication rate and symptom relief, so the synbiotic addition showed no superiority.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 95%
“…Previous meta‐analyses on probiotic‐supplemented triple therapy for H. pylori infection in children showed that the efficacy and safety appeared to be different according to the different probiotics used. Feng et al performed a systemic review and meta‐analysis aiming to identify which probiotic strain or regimen is more effective as a supplementation in H. pylori triple therapy for pediatric populations; 29 trials (3122 participants) involving 17 probiotic regimens were identified. Compared with a placebo, probiotics significantly increased H. pylori eradication rates (relative ratio [RR] 1.19, 95% CI 1.13‐1.25) and reduced the incidence of side effects (RR 0.49, 95% CI 0.38‐0.65).…”
Section: Treatmentmentioning
confidence: 99%
“…Another study suggested the combination of Bacillus mesentericus, Clostridium butyricum, and Streptococcus faecalis as the optimal probiotic regime for reducing side effects and improving eradication rates when supplementing 14‐day triple therapy . Current meta‐analyses suggest that probiotics as an adjunctive therapy increase the cure rate by approximately 10%‐14% . In addition, probiotics are likely to improve compliance and therefore improve eradication rates of triple therapy.…”
Section: Probioticsmentioning
confidence: 99%
“…68 Current meta-analyses suggest that probiotics as an adjunctive therapy increase the cure rate by approximately 10%-14%. [14][15][16][17] In addition, probiotics are likely to improve compliance and therefore improve eradication rates of triple therapy. However, the potential benefit of adding probiotics to more recent and effective combinations (such as concomitant or BQT regimens) has yet to be proven.…”
Section: Prob Iotic Smentioning
confidence: 99%
See 1 more Smart Citation